Pik3r3b, a novel immune-related gene in Nile tilapia (Oreochromis niloticus): Identification, expression and analysis of antibacterial activity. Issue 87 (April 2019) - Meng, Liang; Xu, Wen-teng; Chen, Ya-dong; Wei, Min; Cui, Zhong-kai; Liu, Yang; Guo, Hua; Gan, Xi; Zhu, Jia-jie; Wang, Lin-na; Chen, Song-lin
Abstract: A full-length cDNA encoding phosphatidylinositol 3-kinase regulatory subunit gamma b gene in Nile tilapia ( Oreochromis niloticus ), termed as On-pik3r3b, was identified and characterized in this study. The sequence analysis demonstrated that the full-length cDNA of On-pik3r3b was 2018 bp, containing a 5′ untranslated region (UTR) of 171 bp, an open reading frame (ORF) of 1422 bp and a 3' UTR of 425 bp. Its protein sequence displayed a high degree of identity with other fish. Using qPCR, the expression patterns of On-pik3r3b were investigated. In healthy Nile tilapia, the transcripts of On-pik3r3b were detected in all examined tissues, except the skin. Upon the stimulation with Streptococcus agalactiae, the On-pik3r3b expression level in liver, spleen, kidney and gill were significantly increased at 12 h after infection. The recombinant On-pik3r3b showed in vitro antibacterial activity, against S. agalactiae and E. coli . Our observation strongly indicates that On-pik3r3b is involved in the innate immune response in Nile tilapia.